ТОПОНИМЛАРНИ ГЕОГРАФИК ТАДҚИҚ ЭТИШНИНГ МАНБАЛАРИ ВА УСУЛЛАРИ - Балтабаев, О.О. (SCIENCE and SOCIETY, 2024)
This article covers sources and methods for researching geographic names. The article analyzes the research works of CIS and local scientists who geographically researched toponyms.